The burglar on the prowl - Block, Lawrence (New York : William Morrow, 2004)
Bernie Rhodenbarr, New York bookseller by day and thief by night, is asked by a friend to rob a surgeon who stole his friend's mistress.
Keywords: Rhodenbarr, Bernie (Fictitious character) -- Fiction; Thieves -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction